Some Results of Applying DPSIR Analysis for Ulaanbaatar as Part of the Selenge River Basin Integrated Water Management System - Odontsetseg, D; Janchivdorj, L; Udvaltsetseg, G; Frieden, J (Proceedings of the Mongolian Academy of Sciences, 2011)
Nowadays, ecological problems are being caused by economic aspects, and other hand economic issues are arising from ecological and environmental problems. Therefore, it is important to consider both social and economic factors, and take a basin approach to solving environmental problems. To find a relationship between economy and ecology, complex study of river basins is extremely important in establishing conditions for sustainable development in our country. This paper shows the results of applying DPSIR (Driver-Pressure-State-Impact-Response) analysis for Ulaanbaatar city, undertaken as part of a project on Integrated Water Management for the Selenge River Basin. The DPSIR analysis looks at the linkage between the economy and environment for the water quality and water resources of Ulaanbaatar. We used mDSS4 software to evaluate a range of management responses suggested by these issues and found that charging for pollution and measuring water use would have the largest overall impact on water quality and water resources respectively. The analysis was carried out for Ulaanbaatar, because it was identified as one of the key hotspot areas in the Selenge River Basin, which is the main river basin in Mongolia, in terms of both the economy and natural systems. DOI: http://dx.doi.org/10.5564/pmas.v0i4.43 Proceedings of the Mongolian Academy of Sciences 2009 No 4 pp.22-31